Transcriptional regulation of the c-jun gene by retinoic acid and E1A during differentiation of F9 cells. - Kitabayashi, I (1992)
Differentiation of mouse F9 embryonal carcinoma (EC) cells can be induced by exposure to retinoic acid (RA) or by expression of adenovirus E1A. The transcription of the c-jun gene is stimulated by either RA or E1A. We report here that both RA and E1A strongly induce the expression of chloramphenicol acetyltransferase (CAT) from c-jun promoter/CAT reporter construct (c-jun/CAT), which is stably integrated into F9 cells, in a manner that is independent of both copy number and integration locus. The induction of c-jun/CAT expression is observed in undifferentiated F9 cells, but not in differentiated F9 cells, adenovirus-infected F9 cells or HeLa cells. Deletion analysis of the promoter region of the c-jun gene indicates that the sequence elements required for the RA- and E1A-mediated induction are identical and they have been defined as a region of 145 bp between -190 and -46 of the 5' flanking region of c-jun. This RA and E1A response element (RERE) contains five variants of the motif CGCGGTGACGNT. The upstream two motifs are adjacent and extend in opposite directions, creating an imperfect palindrome. The downstream four motifs are located at 35 or 36 bp intervals in the same orientation. Substitution and insertion analysis indicates that these motifs and their regular intervals are important for the activity of the RERE.